Բայահիմք հասկացության ձևավորման և ամրակայման խնդիրները հանրակրթության մեջ - Հասրաթյան, Ծովինար; Սարգսյան, Վեհանուշ
Սույն հոդվածում նպատակադրվել ենք ներկայացնել բայահիմք ձևաբանական հասկացության հետ կապված հարցերը հանրակրթության մեջ՝ քննելով 7-րդ և 11-րդ դասարանների դասագրքերի տեսական և գործնական նյութը: Վեր ենք հանել դասագրքերում ուսումնական նյութերի ներկայացման մեթոդաբանությունը, առանձնանշել խնդրահարույց կետերը: Մեր կողմից սույն թեմայի ընտրությունը պայմանվորված է նրանով, որ ոլորտի մասնագետների, բանասերների դիտարկումները փաստում են անցյալ կատարյալի հիմքից կազմվող բայաձևերի կառուցվածքային սխալների գոյությունը լեզվակիրների խոսքում: Սխալների շտկման հնարավորությունն ընձեռում է դպրոցը: В статье мы стремились представить вопросы, связанные с морфологическим понятием глагола в общеобразовательной системе, рассмотрели теоретический и практический материал учебников для 7 и 11 классов, а также методологию представления учебных материалов в учебниках, выделили проблемные моменты. Выбор темы обусловлен тем, что специалисты и филологи в данной области свидетельствуют о наличии в речи носителей языка структурных ошибок глагольных форм, образованных на основе прошедшего совершенного времени. Возможность исправления ошибок предоставляется школой. In this article, we tried to present issues related to the morphological concept of the verb in the general education system, considering the theoretical and practical material of textbooks for grades 7 and 11. We considered the methodology for presenting educational materials in textbooks, identified problematic points. We have highlighted that the knowledge of verbs, verb bases, verb forms, expressed meanings, is necessary for the correct formation and use of verb forms in speech. The need for this is explained by the fact that the first prerequisite for the conscious assimilation of the material is to apply the knowledge in practice. Learning grammar definitions alone is not enough to apply them correctly in speech. The reason for the mistake can also be considered insufficient knowledge of the basics of swimming. If the puple does not distinguish between the base of the indefinite past participle and the base of the past perfect, he will make mistakes in the verb forms formed from them. Our choice of this topic is due to the fact that the observations of specialists and philologists in this field indicate the presence of structural errors in verb forms formed on the basis of the past perfect tense in the speech of native speakers. The opportunity to correct errors is provided by the school.
Keywords: Հայոց լեզվի դասավանդման մեթոդիկա